2004
DOI: 10.1056/nejmcp035553
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bacterial Sinusitis

Abstract: The new england journal of medicine n engl j med 351;9 www.nejm.org august 26, 2004 902 This Journal feature begins with a case vignette highlighting a common clinical problem. Evidence supporting various strategies is then presented, followed by a review of formal guidelines, when they exist. The article ends with the author's clinical recommendations.A 43-year-old man has a two-week history of nasal congestion, postnasal drip, and fatigue. He has used an over-the-counter nasal decongestant and acetaminoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 22 publications
1
35
0
5
Order By: Relevance
“…First, due to the invasiveness of the procedure, no respiratory culture information was available to assess the appropriateness of the "choice" of antibiotic. [16][17][18][19] However, the choice of antibiotic was rated as appropriate for effectiveness if the antibiotic choice was consistent with those recommended by national guidelines. Secondly, fewer drug-drug interactions may have been seen because the VA has computerized physician order entry with a database that automatically checks and flags clinically important drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, due to the invasiveness of the procedure, no respiratory culture information was available to assess the appropriateness of the "choice" of antibiotic. [16][17][18][19] However, the choice of antibiotic was rated as appropriate for effectiveness if the antibiotic choice was consistent with those recommended by national guidelines. Secondly, fewer drug-drug interactions may have been seen because the VA has computerized physician order entry with a database that automatically checks and flags clinically important drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to evaluating antibiotic prescribing practices, the MAI instructions were modified to be more specific to antibiotic therapy guidelines for the management of patients with community-acquired pneumonia (CAP), acute exacerbations of chronic bronchitis (AECB), and sinusitis in CAP, sinusitis, and AECB. [16][17][18][19] In addition, MAI instructions for appropriate antibiotic doses for patients with renal impairment and clinically important antibiotic drug interactions were specified using a standard pharmacotherapy information source. 20 The developer of the instrument (JTH) trained the two clinical pharmacists (CCT and SLA) in the use of the modified MAI.…”
Section: Assessment Using the Medication Appropriateness Indexmentioning
confidence: 99%
“…pneumoniae and Hemophilus influenzae are the most common pathogenic bacteria causing acute bacterial sinusitis, accounting for more than 70% of strains [2,16] . Hence, using S. pneumoniae in our study was of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…(12,16,22) Various authors have suggested that, in the identification of patients with sinusitis, symptoms and signs are only nosis. These results provide further evidence that a clinical diagnosis of acute bacterial rhinosinusitis should be made with caution.…”
Section: Discussionmentioning
confidence: 99%